Profiling estrogen, progesterone, and androgen receptors in colorectal cancer in relation to gender, menopausal status, clinical stage, and tumour sidedness - Refaat, Bassem; Aslam, Akhmed; Idris, Shakir; Almalki, Ahmed H.; Alkhaldi, Mofareh Y.; Asiri, Hassan A.; Almaimani, Riyad A.; Mujalli, Abdulrahman; Minshawi, Faisal; Alamri, Sara A.; AlHussain, Mona I.; Baltow, Badee A.; et al. (Frontiers in Endocrinology, 2023)
Although estrogen (ERα/ERβ), progesterone (PGR), and androgen (AR) receptors are pathologically altered in colorectal cancer (CRC), none of the prior studies measured their expression within the same cohort of patients. Herein, ERα/ERβ/PGR/AR proteins were measured in archived paired normal and malignant colon specimens (n =120 patients) by immunohistochemistry, and results were analyzed by gender, age (≤50 vs. ≥60 years), clinical stages (early-stage I/II vs. late-stage III/IV), and anatomical location (right; RSCs vs. left; LSCs). Effects of 17β-estradiol (E2), progesterone (P4), and testosterone alone or combined with the specific blockers of ERα (MPP dihydrochloride), ERβ (PHTPP), PGR (mifepristone), and AR (bicalutamide) on cell cycle and apoptosis were also measured in the SW480 male and HT29 female CRC cell lines. ERα and AR proteins increased, whilst ERβ and PGR declined markedly in malignant specimens. Moreover, male neoplastic tissues showed highest AR expression, whilst ERβ and PGR weakest alongside ERα strongest expression was seen in cancerous tissues from women aged ≥60 years. Late-stage neoplasms also revealed maximal alterations in the expression of sex steroid receptors. By tumor location, LSCs disclosed significant elevations in ERα with marked declines in PGR compared with RSCs, and ERα strongest alongside PGR weakest expression was detected in advanced LSCs from women aged ≥60 years. Late-stage LSCs from females aged ≥60 years also showed weakest ERβ and strongest AR expression. In contrast, male RSC and LSC tissues exhibited equal ERβ and AR expression in all clinical stages. ERα and AR proteins also correlated positively, whereas ERβ and PGR inversely, with tumor characteristics. Concomitantly, E2 and P4 monotherapies triggered cell cycle arrest and apoptosis in the SW480 and HT29 cells, and while pre-treatment with ERα-blocker enhanced the effects of E2, ERβ-blocker and PGR-blocker suppressed the E2 and P4 anti-cancer actions, respectively. In contrast, treatment with the AR-blocker induced apoptosis, whilst co-treatment with testosterone hindered the effects. In conclusion, this study advocates that protein expression of sex steroid receptors in malignant tissues could represent prognostic markers, as well as hormonal therapy could provide an alternative strategy against CRC, and their efficacies could be dependent on gender, clinical stage, and tumor location.